Invisible Adaptation: The Effect of Awareness on the Strength of the Motion Aftereffect. (August 2020) - Roumani, Daphne; Moutoussis, Konstantinos
The ability to process information despite the lack of perceptual awareness is one of the most fascinating aspects of the visual system. Such unconscious processing is often investigated using adaptation, where any presence of the former can be traced by its footprint on aftereffects following the latter. We have investigated the mechanisms of the motion aftereffect (MAE) using random dot displays of varying motion coherence as well as crowding to modulate both the physical as well as the perceptual strength of the adaptation stimulus. Perceptual strength was quantitatively measured as the performance in a forced-choice direction-discrimination task. A motion-nulling technique was used to quantitatively measure the strength of the MAE. We show that the strength of the dynamic MAE is independently influenced by both the physical stimulus strength as well as the subjective perceptual strength, with the effect of the former being more prominent than that of the latter. We further show that the MAE still persists under conditions of subthreshold perception. Our results suggest that perceptual awareness can influence the strength of visual processing, but the latter is not fully dependent on the former and can still take place at its partial or even total absence.